Ontogenetic features of Saposhnikovia divaricate (Turcz.) Schischk. introduced into the environments of the Cis-Baikal Region - E. G. Khudonogova; S. V. Polovinkina (Труды по прикладной ботанике, генетике и селекции)
Background. Saposhnikovia (Saposhnikovia Schischk.) is a monotypic genus occurring in the south of Eastern Siberia, the Far East, Mongolia, Manchuria, and Korea. Saposhnikovia divaricata (Turcz.) Schischk. grows in Baikal Siberia and Transbaikalia, but does not occur in the Cis-Baikal Region. Roots, grass and fruits of S. divaricata are used in Oriental medicine as an anti-inflammatory and antipyretic agent. The species is promising for introduction into domestic medical practice. Currently, its area of distribution is rapidly shrinking due to the uncontrolled collection of roots for medicinal purposes. Plant introduction studies can solve the problem of sustainable utilization and conservation of the species.Materials and methods. Ontogenetic features of S. divaricata were studied in the experimental field of Irkutsk State Agrarian University for three years. The age composition of the species was analyzed according to T. A. Rabotnov’s methodology, taking into account the publications by L. B. Zaugolnova with coauthors and E. L. Nukhimovsky.Results and conclusions. S. divaricata is an aboveground two-seeded semi-deciduous plant; its seed germination rate is 87– 90% in the laboratory, and 85–88% in the field. Its plants in the first year of their life pass through the stages of the pregenerative period and proceed into the winter season in a virginal state. About 6% of the plants enter the generative state in the second year of life, and all the rest do it in the third year. The highest root weight was recorded in virginal plants in their second year of life (12.48 g). S. divaricata is a species of mediocre prospects for introduction into the environments of the Cis-Baikal Region.